EDUKASI INVESTASI GENERASI MILENIA BAGI SISWA SMKS PGRI 3 KOTA SERANG - Rahardian Amrullah; Iroh Rahmawati (TRIDAYA: Jurnal Pengabdian kepada Masyarakat, 2025)
The millennial generation currently faces various unique challenges and problems when it comes to investing. Millennial generation investment education, especially for PGRI 3 Vocational School students in Serang City, is very important to provide understanding to the millennial generation, especially vocational school students, regarding concepts, investment practices and personal financial management so that they can make wiser financial decisions in the future. The increase in young investors needs to be balanced with strong knowledge and understanding of financial literacy. This is because the level of financial literacy and investment strategies among millennials is relatively low. Research from the Financial Services Authority (OJK) shows that the literacy rate for millennials aged 18-25 years is only 32.1 percent. Meanwhile, millennials aged 25-35 years were 33.5 percent. The methods used in PKM activities are counseling and class discussions, investment simulation games, and case studies. It is designed to provide students with a more practical and interactive understanding. The results of this PKM activity show that structured and comprehensive investment education is effective in increasing the financial literacy and investment readiness of the millennial generation. Recommendations are given for implementing similar programs in other schools to support the development of financial literacy among the younger generation